Collaborative model of care between Orthopaedics and allied healthcare professionals in knee osteoarthritis (CONNACT) : study protocol for an effectiveness-implementation hybrid randomized control trial - Tan, Bryan Yijia (2021)
Background: Knee Osteoarthritis (OA) is a leading cause of global disability. The Collaborative Model of Care between Orthopaedics and Allied Healthcare Professionals (CONNACT) Model of Care (MoC) was developed by optimizing evidence-based non-surgical treatments to deliver value-based care for people with knee OA. The primary aim of this study is to determine the clinical effectiveness of the CONNACT MoC (3 months) compared to usual care. The secondary aims are: a) To determine the cost-effectiveness and b) To develop an evaluation and implementation framework to inform large scale implementation for this MoC. Methodology: Type 1 Effectiveness-Implementation Hybrid Trial using an explanatory sequential mixed-method approach. The study consists of 3 components. The first component is the pragmatic, parallel-arm, single-blinded randomized control trial. Inclusion criteria are patients with knee OA based on the National Institute of Health and Care Excellence (NICE) criteria with radiographic severity of greater than Kellgren-Lawrence 1, and Knee Injury and OA Outcome Score (KOOS4) of equal or less than 75. Exclusion criteria include other forms of arthritis, history of previous knee arthroplasty or wheelchair-bound patient. KOOS4 is the primary outcome measure at 3 months, 6 months and 1 year. Secondary outcomes include KOOS individual subscales, quality of life scoring, functional performance, global, diet and psychological related outcomes. The second component is an economic evaluation of the cost-effectiveness of the CONNACT MoC using a societal perspective. The third component is an implementation and evaluation framework using process evaluation under the RE-AIM framework using a mixed-method approach. Sample size of 100 patients has been calculated. Discussion: CONNACT MoC is a complex intervention. In line with the MRC guidance for developing and evaluating complex interventions, a pilot feasibility study was completed and a comprehensive approach including an RCT, economic evaluation and process evaluation is described in this study protocol. Results from this study will help clinicians, healthcare administrators and policymakers guide the sustainable and effective implementation of the CONNACT MoC for knee OA and serve as a basis for similar multidisciplinary MoC for chronic degenerative musculoskeletal conditions to be developed.